Espaktasi Pengelolaan Tanah Terlantar Oleh Baitul Mal Dalam Peningkatan Kesejahteraan Masyarakat - Ulya, Zaki (UI Scholars Hub, 2016)
Baitul Mal is an institution that is authorized as property manager religion formed on the basis of specificity Aceh in implementing Islamic law. Baitul Mal authority in managing the wealth of religion stipulated in Qanun No. 10 of 2007 about Baitul Mal, where one authority Baitul Mal is managing the property / land owners and their heirs abandoned. Abandoned land owners and their Heirs applicable reference to the provisions referred to as a wasteland controlled by the state. In deed the management of abandoned land intended to improve the welfare of the community, which can be managed by the Baitul Mal. This is certainly in line with the mandate of Act No. 2 of 2012. However, the exercise of powers Baitul Mal becomes constrained due to the lack of clear regulations and cons of authority by the National Land Agency. If the Baitul Mal authority to manage wastelands clear with innovative concepts will realize expectations better for public welfare.